Phytase activity in lichens - Higgins, Niall F.; Crittenden, P.D. (Wiley, 2015)
Phytase activity was investigated in 13 lichen species using a novel assay method. The work tested the hypothesis that phytase is a component of the suite of surface-bound lichen enzymes that hydrolyse simple organic forms of phosphorus (P) and nitrogen (N) deposited onto the thallus surface. Hydrolysis of inositol hexaphosphate (InsP6, the substrate for phytase) and appearance of lower-order inositol phosphates (InsP5–InsP1), the hydrolysis products, were measured by ion chromatography. Phytase activity in Evernia prunastri was compared among locations with contrasting rates of N deposition. Phytase activity was readily measurable in epiphytic lichens (e.g. 11.3 lmol InsP6 hydrolysed g-1 h-1 in Bryoria fuscescens) but low in two terricolous species tested (Cladonia portentosa and Peltigera membranacea). Phytase and phosphomonoesterase activities were positively correlated amongst species. In E. prunastri both enzyme activities were promoted by N enrichment and phytase activity was readily released into thallus washings. InsP6 was not detected in tree canopy throughfall but was present in pollen leachate. Capacity to hydrolyse InsP6 appears widespread amongst lichens potentially promoting P capture from atmospheric deposits and plant leachates, and P cycling in forest canopies. The enzyme assay used here might find wider application in studies on plant root–fungal–soil systems.